2004
DOI: 10.3168/jds.s0022-0302(04)73467-0
|View full text |Cite
|
Sign up to set email alerts
|

Resynchronizing Estrus with Progesterone or Progesterone Plus Estrogen in Cows of Unknown Pregnancy Status

Abstract: Two experiments were conducted to test 2 progesterone (P4)-based treatments that were applied to lactating dairy cattle of unknown pregnancy status to resynchronize estrus of nonpregnant cows. In experiment 1, cows were assigned randomly before a timed AI (TAI) to 1) treatment with a CIDR (controlled internal drug-releasing intravaginal insert containing P4) for 7 d starting on d 13 after TAI (CIDR; n = 300) or 2) no P4 treatment (control; n = 330). Compared with controls, P4 increased the synchrony of those d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
36
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 39 publications
7
36
0
4
Order By: Relevance
“…In the present study, PRs for the first eligible oestrus after CIDR removal were not different on day 30 which are in agreement with the results reported by Rivera et al (2005) and Colazo et al (2006) on day 30 in dairy and beef heifers and by El-Zarkouny and Stevenson (2004) on day 29 in dairy cows. On the other hand, PRs on day 55 post TAI in the present study were numerically higher (not significant) in CGPG group than in the control which are in agreement with the results of Hanlon et al (1997) who reported a similar PR to a resynchronised oestrus in dairy heifers using CIDR device for 5 days beginning 14 or 16 days after AI.…”
supporting
confidence: 93%
“…In the present study, PRs for the first eligible oestrus after CIDR removal were not different on day 30 which are in agreement with the results reported by Rivera et al (2005) and Colazo et al (2006) on day 30 in dairy and beef heifers and by El-Zarkouny and Stevenson (2004) on day 29 in dairy cows. On the other hand, PRs on day 55 post TAI in the present study were numerically higher (not significant) in CGPG group than in the control which are in agreement with the results of Hanlon et al (1997) who reported a similar PR to a resynchronised oestrus in dairy heifers using CIDR device for 5 days beginning 14 or 16 days after AI.…”
supporting
confidence: 93%
“…Variations on this basic "double" treatment regimen have been tested with Holsteins in American herds with variable results. ElZarkouny and Stevenson [27] as well as Chebel et al [21] both reported that the post-insemination use of an ivagP4 insert could reduce pregnancy loss through increased embryo survival rate from around Day 30 to Day 60 post-insemination. However, little cognisance has been given to the likely reasons for any effects, given the limited effect of the invagP4 inserts to significantly increase plasma concentrations of progesterone in large, high producing lactating Holstein cows.…”
Section: Treating Anestrus In Lactating Dairy Cowsmentioning
confidence: 99%
“…The CIDR inserts increased embryo survival between days 29 and 57 post-TAI when treatment for 7 days starting on Day 13 post-TAI was performed [99]. Similarly, PRID also improved PR when used from Day 10 post-AI for 7 days [87].…”
Section: Preventive Pharmaceutical Treatment In Mid Luteal Phase Post-aimentioning
confidence: 89%